Superior Sodium Metal Anodes Enabled by 3D Hierarchical Metallic Scaffolds with Enhanced Sodiophilicity - Chong Chen; Rui Yang; Jie Zhu; Wenjiao Yao; Yongbing Tang (Advanced Science, 2025)
Abstract Sodium‐metal batteries (SMBs) are regarded as key for next‐generation energy storage due to their high theoretical energy and potential cost effectiveness. However, Na‐metal systems remain challenging by critical barriers, including severe Na dendrites growth and infinite huge volume change, which limit the feasibility of SMBs. Here, this work develops a 3D conductive scaffold consisting of vertical crystalline TiO2 nanotube arrays embedded with ultrafine silver nanoparticles (denoted as Ag@TiO2 NTAs) with ultrasonication‐assisted in situ deposition method for high‐performance SMBs. Significantly, the hierarchical hollow nanotubes with large surface area can reduce the current density to promote compact electrodeposition and guide the parallel growth of Na. Meanwhile, the sodiophilic Ag nanocrystals with strong interactions with Na+ enable a marked reduction of the nucleation barriers. As a result, the Na metal anode with the Ag@TiO2 NTAs host delivers remarkable electrochemical properties including ultralow voltage hysteresis and prolonged cycling stability over 3600 h. By pairing with a Na3V2(PO4)3 cathode, the SMBs achieve 87% capacity retention after 2000 cycles at 8 C, suggesting its potential application for highly stable Na anodes.